2022
DOI: 10.21203/rs.3.rs-2070537/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation between the expression of lipids in the inner membrane complex of Toxoplasma gondii and its virulent phenotypes

Abstract: Toxoplasma gondii, a highly prevalent obligate apicomplexan parasite, is important in clinical and/or veterinary medicine. Based on its virulence in laboratory mouse strains, T. gondii is divided into three lineages. In this study, we examined and compared the distributions of the glycerophospholipids phosphatidylserine (PtdSer) and phosphatidylethanolamine (PtdEtn) and a glycosphingolipid GM3 in type I RH and type II PLK strains of T. gondii (highly and moderately virulent phenotypes, respectively). The gold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…In T. gondii tachyzoites, while PtdThr and PtdIns are implicated in regulating calcium signaling and homeostasis in tachyzoites ( 4 , 7 ), PtdOH and PtdSer promote microneme exocytosis and gliding motility in response to calcium signaling ( 5 , 8 ), The PSS-depleted mutant also suggests a role of PtdSer in regulating the locomotion of tachyzoites. A recent study deployed electron microscopy (quick-freeze-fracture replica labeling) to determine the distribution of PtdSer and PtdEtn in parasite membrane leaflets ( 42 ). The authors observed that both lipids are primarily localized in the luminal leaflet of the inner membrane complex (IMC), located just underneath the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In T. gondii tachyzoites, while PtdThr and PtdIns are implicated in regulating calcium signaling and homeostasis in tachyzoites ( 4 , 7 ), PtdOH and PtdSer promote microneme exocytosis and gliding motility in response to calcium signaling ( 5 , 8 ), The PSS-depleted mutant also suggests a role of PtdSer in regulating the locomotion of tachyzoites. A recent study deployed electron microscopy (quick-freeze-fracture replica labeling) to determine the distribution of PtdSer and PtdEtn in parasite membrane leaflets ( 42 ). The authors observed that both lipids are primarily localized in the luminal leaflet of the inner membrane complex (IMC), located just underneath the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Konishi et al. found that PtdSer is mainly confined to the cytoplasmic leaflet of the middle IMC membrane, while it was absent in the cytoplasmic leaflet of the inner IMC membrane ( 42 ). The data suggest a barrier-like mechanism preventing diffusion of PtdSer in the cytoplasmic leaflets of the two membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation